2015
DOI: 10.2337/db14-1937
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mitochondrial Biogenesis in Adipose Tissue in Acquired Obesity

Abstract: Low mitochondrial number and activity have been suggested as underlying factors in obesity, type 2 diabetes, and metabolic syndrome. However, the stage at which mitochondrial dysfunction manifests in adipose tissue after the onset of obesity remains unknown. Here we examined subcutaneous adipose tissue (SAT) samples from healthy monozygotic twin pairs, 22.8-36.2 years of age, who were discordant (ΔBMI >3 kg/m(2), mean length of discordance 6.3 ± 0.3 years, n = 26) and concordant (ΔBMI <3 kg/m(2), n = 14) for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
237
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 289 publications
(267 citation statements)
references
References 46 publications
15
237
0
3
Order By: Relevance
“…16 The participants have been described previously as has the targeted analysis of genes regulating the mitochondria. 11,12 In brief, the mean BMI difference within the twin pairs was 6 kg m − 2 , and mean age 30.2 years at the time of clinical study. The twins were healthy, with the exception of one obese twin with inactive ulcerative colitis (treated with mesalazine and azathioprine), and another obese twin with T2DM (treated with metformin and insulin).…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…16 The participants have been described previously as has the targeted analysis of genes regulating the mitochondria. 11,12 In brief, the mean BMI difference within the twin pairs was 6 kg m − 2 , and mean age 30.2 years at the time of clinical study. The twins were healthy, with the exception of one obese twin with inactive ulcerative colitis (treated with mesalazine and azathioprine), and another obese twin with T2DM (treated with metformin and insulin).…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
“…17 We also recorded nutritional intake with a 3-day food diary, physical activity by Baecke indices. 12,20 Current daily smoking status for the twins was assessed by questionnaire.…”
Section: 17mentioning
confidence: 99%
See 2 more Smart Citations
“…This paper is under submission. A recent study with human twins showed that adiposity is correlated with downshifting of fatty acid oxidation and that, indeed, mitochondrial biogenesis, oxidative metabolic pathways and OXPHOS proteins in subcutaneous adipose tissue are down regulated in acquired obesity [89]. Thus, WAT FAO stimulation can be considered a target to develop therapies for prevention and treatment of obesity, insulin resistance and related pathologies via energy expenditure augmentation and fat loss.…”
Section: Mitoneet Inhibitionmentioning
confidence: 99%